Forearm and tibial bone measures of distance- and sprint-trained master cyclists - Wilks, D. C.; Gilliver, S. F.; Rittweger, J. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Cycling is very popular; however, it is often believed to be associated with below average bone mass. This study compared bone measures of sprint- and distance-trained cyclists competing at World Master Track Championships, along with sedentary controls (30-82 yr), and examined the associations of bone measures with age.